2000
DOI: 10.1046/j.1471-4159.2000.0751092.x
|View full text |Cite
|
Sign up to set email alerts
|

Facilitatory Roles of Novel Compounds Designed from Cyclopentenone Prostaglandins on Neurite Outgrowth‐Promoting Activities of Nerve Growth Factor

Abstract: Cyclopentenone prostaglandins (PGs) are known to arrest the cell cycle at the G 1 phase in vitro and to suppress tumor growth in vivo. However, their effects on neurons are unclear. Here, we report that some cyclopentenone PGs function as neurite outgrowth-promoting factors. They promoted neurite outgrowth from PC12 cells and from dorsal root ganglion explants but only in the presence of nerve growth factor (NGF). We refer to these PGs as neurite outgrowth-promoting PGs (NEPPs). Through study of the structure-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 46 publications
0
42
0
Order By: Relevance
“…These authors also found neuroprotective effects of CDDO methylamide in 3-nitropropionic acid rat and MPTP (1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine) mouse models (Yang et al, 2009). Other intriguing neuroprotective agents that induce Hmox1 expression by this mechanism include the electrophilic neurite outgrowth-promoting prostaglandin compounds (Satoh et al, 2000).…”
Section: Polyphenols and Other Natural Productsmentioning
confidence: 88%
“…These authors also found neuroprotective effects of CDDO methylamide in 3-nitropropionic acid rat and MPTP (1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine) mouse models (Yang et al, 2009). Other intriguing neuroprotective agents that induce Hmox1 expression by this mechanism include the electrophilic neurite outgrowth-promoting prostaglandin compounds (Satoh et al, 2000).…”
Section: Polyphenols and Other Natural Productsmentioning
confidence: 88%
“…Male ob/+ and ob/ob mice (8 wk old) were anesthetized with Aerane (Baxter) and injected through the penis vein with 10 8 PFU/g BW of Ad β-gal or Ad GRP78 in a final volume of 250 μl sterile physiological serum. Ad GRP78 was constructed as described previously by Satoh et al (55). Adenoviruses were amplified in HEK 293 cells and purified on a cesium chloride gradient.…”
Section: Figure 12mentioning
confidence: 99%
“…It is also reported that CDDO-MA has neuroprotective effects in 3-nitropropionic acid (3-NP) rat and MPTP mouse models [87]. Other intriguing neuroprotective agents that induce Hmox1 expression by this mechanism are the electrophilic neurite outgrowth-promoting prostaglandin (NEPP) compounds [88]. …”
Section: Introductionmentioning
confidence: 99%